MOBILE CARWASH BUSINESS FEASIBILITY ANALYSIS IN THE CITY OF MEDAN - Nayla Sari Yusri (Proceeding International Seminar of Islamic Studies, 2023)
The intensity of purchasing motorized vehicles can increase the need for motor vehicle maintenance. Currently needed a place of care motorized vehicles, one of which is an effective and efficient car wash, which is effective in terms of customer service, namely doing it carefully the process of washing the exterior and interior of the car, while efficient in terms of costs and service waiting times. So, to be able to meet the needs the maintenance of car-type motorized vehicles is applied to the Mobile concept Carwash. However, there are some problems in setting up a mobile business Carwash, which requires a fairly large and owned capital investment business risk. It takes a planning stage so that the business will built has a minimum risk, including the need to conduct a study feasibility which includes market aspects, technical aspects, legal aspects, sources aspects human resources, financial aspects, and sensitivity analysis to several parameters that may affect the current viability of the business.Based on results of business feasibility analysis for each aspect, all aspects are stated meet the eligibility criteria.